The Functioning of the Open Economy – Mundell-Fleming Model - Kuta, Katarzyna; Rudnicki, Krzysztof (Journal of Finance and Financial Law, 2015)
This article is focused on presenting the Mundell-Fleming model as a tool that provides help in analyze of the influence of different mixes of fiscal and monetary policies (policy mix) on economy. The elaboration is based on an assumption of significance of the data generated in a process of MF model analysis on macroeconomic variables. In the article there are presented either theoretical assumption of the model and possible output of using different policy mix.